Germinal Matrix-Intraventricular Hemorrhage: A Tale of Preterm Infants - Walufu Ivan Egesa; Simon Odoch; Richard Justin Odong; Gloria Nakalema; Daniel Asiimwe; Eddymond Ekuk; Sabinah Twesigemukama; Munanura Turyasiima; Rachel Kwambele Lokengama; William Mugowa Waibi; Said Abdirashid; Dickson Kajoba; et al. (Hindawi Limited, 2021)
Germinal matrix-intraventricular hemorrhage (GM-IVH) is a common intracranial complication in preterm infants, especially those born before 32 weeks of gestation and very-low-birth-weight infants. Hemorrhage originates in the fragile capillary network of the subependymal germinal matrix of the developing brain and may disrupt the ependymal lining and progress into the lateral cerebral ventricle. GM-IVH is associated with increased mortality and abnormal neurodevelopmental outcomes such as posthemorrhagic hydrocephalus, cerebral palsy, epilepsy, severe cognitive impairment, and visual and hearing impairment. Most affected neonates are asymptomatic, and thus, diagnosis is usually made using real-time transfontanellar ultrasound. The present review provides a synopsis of the pathogenesis, grading, incidence, risk factors, and diagnosis of GM-IVH in preterm neonates. We explore brief literature related to outcomes, management interventions, and pharmacological and nonpharmacological prevention strategies for GM-IVH and posthemorrhagic hydrocephalus.